Integer programming and combinatoral optimization 15th International Conference, IPCO 2011, New York, NY, USA, June 15-17, 2011, proceedings - Gunluk, Oktay; Woeginger, Gerhard J. (Lecture notes in computer science, 2011)
This book constitutes the proceedings of the 15th International Conference on Integer Programming and Combinatorial Optimization, IPCO 2011, held in New York, USA in June 2011. The 33 papers presented were carefully reviewed and selected from 110 submissions. The conference is a forum for researchers and practitioners working on various aspects of integer programming and combinatorial optimization with the aim to present recent developments in theory, computation, and applications. The scope of IPCO is viewed in a broad sense, to include algorithmic and structural results in integer programming and combinatorial optimization as well as revealing computational studies and novel applications of discrete optimization to practical problems.